ANALISIS RADIASI MEDAN ELEKTROMAGNETIK YANG DITIMBULKAN OLEH TELEPON SELULER BERDASARKAN VARIASI DAYA BATERAI - Situmorang, Rosnalia Agnes; Mislan, Mislan; Rinaldi, Aditya (GEOSAINS KUTAI BASIN, 2020)
ABSTRACT The research has been conducted on the analysis of electromagnetic field radiation caused by mobile phones. Based on battery power differences. The measurements were made on July 25, 2019, July 26, 2019, July 27, 2019 at the Instrumentation Laboratory at the Faculty of Mathematics and Natural Sciences, Molwarman University, from 8:00 to 16:00. The measurement method used is frequent measurements using the QX-5 electromagnetic field tester on each type of mobile phone, which is already identified. The results showed that the radiation intensity in the three mobile phone brands had radiation intensity values lower than the threshold value of 10 MW / cm 2. From data analysis, it was found that the mobile phone with the highest electromagnetic radiation intensity was the Samsung J2 Prime mobile phone while The smallest phone Vivo Pro 15 Vivo mobile. Mobile phone battery that has the highest value of electromagnetic wave intensity in weak battery power is 25% < DB ≤ 50%, the mobile phone use distance that has the highest electromagnetic radiation intensity is at a distance of 0 cm and 3 cm and a good distance in the use of mobile phone It is 6 cm, 9 cm, 12 cm, the greatest intensity of electromagnetic wave radiation during use or making a phone call whatsapp.